2007
DOI: 10.1063/1.2710474
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic properties and exciplex emission of polyphenylenevinylene-based blend solar cells

Abstract: By studying the photoluminescence emission and photovoltaic properties of blends of polyphenylenevinylene (PPV)-based electron donating and accepting polymers, the authors observed a strict anticorrelation between relative exciplex emission in the solid state and photovoltaic efficiency of corresponding blend devices. Comparative studies on defined bilayer geometries showed that the overall shape of the current-voltage characteristics under illumination is independent of device geometry and layer thickness. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 16 publications
10
98
0
Order By: Relevance
“…Independently from each other, Offermans et al and Morteani et al found evidence for the formation of exciplex states at polymer:polymer interfaces. 17,18 Their findings were recently confirmed by Yin et al 19 The importance of the exciplex decay channel strongly depends on the details of the state diagram and the rate constants of the transitions between these states. From these studies, [17][18][19] it is concluded that the generation of free charges is field and temperature dependent and competes with exciplex decay (via exciplex emission and/or population of the lowest T 1 state of the polymers).…”
Section: Exciton Dissociation (H Ed )supporting
confidence: 63%
See 1 more Smart Citation
“…Independently from each other, Offermans et al and Morteani et al found evidence for the formation of exciplex states at polymer:polymer interfaces. 17,18 Their findings were recently confirmed by Yin et al 19 The importance of the exciplex decay channel strongly depends on the details of the state diagram and the rate constants of the transitions between these states. From these studies, [17][18][19] it is concluded that the generation of free charges is field and temperature dependent and competes with exciplex decay (via exciplex emission and/or population of the lowest T 1 state of the polymers).…”
Section: Exciton Dissociation (H Ed )supporting
confidence: 63%
“…Yin et al compared polymer bilayer and polymer blend devices (using M3EH-PPV or MEH-M3EH-PPV as donor and CN-ether-PPV as acceptor polymer). 19 They concluded that the photocurrent in polymer blend devices is mainly determined by charge carrier generation rather than by charge carrier recombination. One can speculate that the picture that may emerge from the above mentioned optical and transport measurements is one where the dissociation of the exciton mainly determines the quantum efficiency of the polymer blend PV device.…”
Section: Charge Collection (H CC )mentioning
confidence: 99%
“…This correlation is consistent with a recent study of PPV-based polymer/polymer blends, which observed as inverse correlation between exciplex-like emission (indicative of significant geminate recombination), and PV device efficiency. 32 We note that our studies of device performance for this polymer series are relatively limited, and that other factors (blend composition, annealing, electric fields from the electrodes) are also likely to impact significantly upon device performance (see for example Ref 89). It has for example been shown that the application of electric fields can assist the dissociation of analogous, luminescence BRPs (referred to therein as 'exciplex') in polymer/polymer blend films.…”
Section: -----<<< Scheme 1 >>>-----mentioning
confidence: 99%
“…36 In particular, in a study employing three different PPV-based polymers, an inverse correlation was observed between this exciplex-like emission strength and PV device performance. 32 However, a clear understanding of the parameters determining the efficiency of charge dissociation versus geminate recombination in organic blend films is yet to be established. Moreover such studies have not previously focused on polythiophene materials, the polymer class currently attracting the greatest interest for efficient organic PV cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, electron-hole ͑e-h͒ pairs generated in this way are still strongly bound by Coulomb interaction and need to be dissociated into free carriers in order to be collected at the electrodes. 1,2 The occurrence of such an interfacial geminate charge pair has been spectroscopically observed for polymer:polymer systems 3,4 and recently also for polymer:fullerene blends. 5 In addition, a strong indication for the existence of a bound e-h pair in polymer:fullerene blends is the field and temperature dependence of the photocurrent at reverse bias.…”
Section: Introductionmentioning
confidence: 99%